PENGARUH ETIKA DAN INTEGRITAS TERHADAP PENYIMPANGAN PADA ANGGOTA POLISI DI INDONESIA - Tugimin Supriyadi; Adinda Putri Dewi, Wanda Fitri Berliana, Putri Fairuz Hidayat, Ira Dinanti Hariyanto (CV. Adiba Aisha Amira, 2024)
The influence of ethics and integrity on police misconduct is an important topic in security and social justice in Indonesia. This journal examines the influence of ethics and integrity on police misconduct in Indonesia, including abuse of power, corruption and human rights violations. This is a serious issue that affects public trust in police institutions. The application of ethics and integrity in police practice and how this influences the level of police misconduct remains a challenge. The aim of this research is to identify types of deviance by police officers and to provide recommendations on how to improve the ethics and integrity of police officers in order to minimize deviant behavior. This research uses qualitative methods by collecting data from relevant sources through literature searches in academic databases and digital libraries. The research results show that ethics and integrity have a significant influence on deviance among police officers. Police officers who have strong ethics and integrity are less likely to engage in deviant behavior. On the other hand, police officers who have weak ethics and integrity are more susceptible to deviant behavior. Therefore, it is important to strengthen the ethics and integrity of police officers through various efforts, such as education and training, leadership, organizational culture, and supervision systems, so as to reduce deviant behavior within the organization.